The shining : Illuminating philosophy and futures studies - Virmajoki, Veli (Elsevier, 2026)
In this paper, I analyze the connections between philosophy and futures studies. I write from the perspective of contemporary analytic philosophy of science, which analyzes fields of inquiry by focusing on their actual practices, methods, conceptual structures, and the ontological and epistemological assumptions embedded in them. I argue for a pragmatic and structured approach that clarifies the field’s methods, concepts, and both ontological and epistemic aspects. Futures studies faces several methodological and conceptual challenges that invite philosophical attention, yet philosophical analysis is easily distracted by abstract debates about issues such as metaphysical nature of time and possibility rather than issues that concern futures studies as it is. I distinguish between philosophy of futures studies, which analyzes how the field generates knowledge and what ontological assumptions about reality are implicit in its practices, and philosophy in futures studies, where philosophical insights contribute to futures studies itself. I argue that there are several core questions in philosophy of futures studies and suggest ways to approach them by using tools built in philosophy of science. I also discuss conceptual engineering as way of conducting philosophy. By prioritizing analytical precision over grand metaphysical speculation, this paper outlines a development strategy for a philosophy of futures studies that offers systematic tools for examining the issues within the field rather than general philosophical questions that are not unique to the field.